A knowledge-based service approach for human-centered robots - Omar, Faruque Sarker M.; Park, J.-M.; Kim, C.; You, B.-J. (Proceedings - IEEE International Workshop on Robot and Human Interactive Communication, 2007)
This paper proposes a knowledge-based approach for adopting user's preferences and policies to plan and execute various services by a human-centered robot. To create an image of an obedient assistant in user's mind, we have suggested developing a robot that can customize its services according to user's guidelines. For materializing our idea, we have presented our Knowledge-Based Human-centered (KBH) architecture. Using the deductive database technology, we have also presented some results demonstrating how our robot can take the high-level knowledge of user's guidelines into account and plan and execute an object delivery service accordingly. ？2007 IEEE.